Reproductive Attitudes of Russian Students: Factors of Conceptualization - Bagirova, Anna; Voroshilova, Anzhelika; Shubat, Oksana (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper is devoted to the results of empirical studies of dynamics of reproductive attitudes and family orientations of youth in the Urals during the last decades. It is stressed that in spite of leading positions of family in the hierarchy of values of modern youth, children as a value obtain lower rank position in this hierarchy. The vast majority of young people are focused on two-child family model. Special attention is paid to such factors of actualization of reproductive attitudes of young people, including students, like gender, age, level of urbanization, place of residence before entering the high school, and etc., as well as the problems of formation of the young generation’s attitudes towards the parental work and the role of state in realization of these attitudes.